Haze and its impact to paddy monitoring from remote sensing satellites - Ahmad, A. (World Academy of Research in Science and Engineering, 2020)
Haze is a common phenomenon in Malaysia and is caused by smoke which originates from forest fires in neighbouring countries. It causes visibility to drop, therefore affecting agricultural monitoring from remote sensing satellites. Such scenarios have caused problems in monitoring crops particularly those having short growth duration such as paddy. This study aims to investigate the haze scenarios in Malaysia and its impact on paddy monitoring from remote sensing satellites. The study makes use of visibility data and Landsat satellite imagery over Malaysia from 1999 to 2008. The result shows that within this period, the 2008 planting season was the most affected by haze where 9 out of 10 satellite overpasses occurred during the conditions where visibility was 10 km or less. Â© 2020, World Academy of Research in Science and Engineering. All rights reserved.